Focal Segmental Glomerulosclerosis Presenting as Acute Systolic Heart Failure - Mosseri, Maurice; AlBayati, Asseel; Udongwo, Ndausung; Alsaadi, Ennis; Patel, Swapnil; Sen, Shuvendu; Asif, Arif (Archives of Clinical and Medical Case Reports, 2021)
Cardiomyopathies are present in many forms and are the result of numerous etiologies with one well-established etiology being chronic kidney disease (CKD). With recent discoveries linking early stages of CKD to profound cardiovascular disease (ischemic or non-ischemic cardiomyopathy), our focus has shifted to a seemingly inexplicable link between focal segmental glomerulosclerosis (FSGS) and non-ischemic cardiomyopathy. The cardiovascular and renal organ systems possess a unique relationship which we presume to be a bi-directional association of cause-and-effect. We present two cases in which our patients, with underlying FSGS, present with signs and symptoms of systolic heart failure.